Zones of Exclusion: Urban Spatial Policies, Social Justice, and Social Services - Bancroft, Karen H. (2012)
Across the United States homeless persons, prostitutes, and drug and alcohol users are subject to policies that severely limit their freedom of movement. These new policies create spatial exclusion zones that deny these groups the right to inhabit or traverse large areas of their cities, particularly in the downtown cores, where treatment centers, shelters, food banks, soup kitchens, government services, and other social services are typically concentrated. In this paper, I examine these new spatial exclusionary policies (with a focus on Washington State's policies), present a brief historical account of socio-spatial practices, contextualize the current spatial laws, and end with the implications of current exclusionary laws for social work practice, policy, and research